2021
DOI: 10.1007/s10902-021-00398-x
|View full text |Cite
|
Sign up to set email alerts
|

Do Psychological Needs Play a Role in Times of Uncertainty? Associations with Well-Being During the COVID-19 Crisis

Abstract: Across the world, measures were taken to contain the spreading of the COVID-19 virus. Many of these measures caused a sudden rupture in people’s daily routines, thereby eliciting considerable uncertainty and potentially also hampering the satisfaction of individuals’ psychological needs for autonomy, relatedness, and competence. Drawing upon Maslow’s Hierarchical Need Theory and Self-Determination Theory, this study examined the unique role of felt insecurity and the psychological needs, as well as their dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 69 publications
(99 reference statements)
10
74
0
Order By: Relevance
“…Similar to prior research, stress of COVID-19 was positively associated with college students' EI (Vermote et al, 2021 ). Based on Maslow's prepotency principle, it can be expected that both in peaceful and stable conditions, such as during vacation periods, as well as in distressing and unstable conditions, such as during the COVID-19 crisis, these needs might play a predictive role (Maslow, 1970 ; Vansteenkiste et al, 2020 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar to prior research, stress of COVID-19 was positively associated with college students' EI (Vermote et al, 2021 ). Based on Maslow's prepotency principle, it can be expected that both in peaceful and stable conditions, such as during vacation periods, as well as in distressing and unstable conditions, such as during the COVID-19 crisis, these needs might play a predictive role (Maslow, 1970 ; Vansteenkiste et al, 2020 ).…”
Section: Discussionsupporting
confidence: 86%
“…However, COVID-19 can elicit a lot of worry and insecurity in individuals (Brodeur et al, 2021 ), including uncertainty regarding one's health (e.g., Mertens et al, 2020 ) and economic concerns (e.g., Fetzer et al, 2020 ; Kleinberg et al, 2020 ). From a Maslowian perspective, when strong concerns for safety/security become salient, such concerns would play a preeminent role in individuals' functioning, leaving less room for other needs in the need-hierarchy, such as those studied in Self-Determination Theory (SDT), to play a supplementary role (Vermote et al, 2021 ). However, if the living environment cannot satisfy the basic needs, individuals may adapt poorly or switch to other resources to satisfy.…”
Section: Introductionmentioning
confidence: 99%
“…Koestner and Holding further suggested that SDT's emphasis on autonomy has a particular salience in this age of COVID-19 in which voluntary compliance matters to public health. We agree, and have seen SDT's ability to differentiate between autonomy and "freedom," and to identify strategies that facilitate maintained behavior change to be highly relevant in this pandemic (e.g., Martela et al, 2021;Vermote et al, 2021).…”
mentioning
confidence: 69%
“…Koestner and Holding further suggested that SDT's emphasis on autonomy has a particular salience in this age of COVID-19 in which voluntary compliance matters to public health. We agree, and have seen SDT's ability to differentiate between autonomy and "freedom," and to identify strategies that facilitate maintained behavior change to be highly relevant in this pandemic (e.g., Martela et al, 2021;Vermote et al, 2021).Concerning this emphasis on autonomy, Sheldon and Geoffredi (2021) worried that SDT faces a "major threat" from determinists who object to "free will." Yet we suggest that sophisticated determinism is not at all a threat to SDT's organismic approach.…”
mentioning
confidence: 84%
“…The first COVID-19 lockdown in Switzerland exposed people to novel circumstances, which presented challenging stressors that had severe impacts on psychological balance and well-being ( Kuhn et al, 2021 ; Gubler et al, 2021 ; Peterson et al, 2021 ). Societal and economic lockdown measures imposed substantial burdens on people worldwide, resulting in increased anxiety and depressive emotions ( Burhamah et al, 2020 ; Xiong et al, 2020 ; Mencaccia and Salvi, 2021 ; Passavanti et al, 2021 ; Vermote et al, 2021 ). During pandemic conditions, psychological strain can be caused by social isolation due to contact restrictions, quarantine measures, school and company closures, and related negative career impacts such as becoming unemployed ( Blustein and Guarino, 2020 ; Prati, 2020 ; Serafini et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%